PENERAPAN PSAK NO.34 DALAM PENGAKUAN PENDAPATAN JASA KONSTRUKSI PADA PT. ADHI KARYA (PERSERO) Tbk SURABAYA - Ashari, Rizky Kurniawan (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
In the construction company there are specific things in determining the timing of income. The implementation of the revenue recognition has no influence to the companyâs cash flow. This research is carried out to find out the suitability of the implementation of revenue recognition at PT. Adhi Karya (Persero) Tbk Divisi Konstruksi IV Surabaya by using Accounting Standard Statement (PSAK) No. 34 about the Constructions Contract Accounting. Descriptive method is used as analysis method which describes a condition objectively so the solution of a problem that is encountered by the company is obtained. The results of this study show that PT. Adhi Karya (Persero) Tbk Divisi Konstruksi IV Surabaya in recognizing their construction service revenue has been using completion percentage method that is suitable with Accounting Standard Statement (PSAK) No. 34 about the Construction Contract Accounting.Keywords: Revenue, Revenue Recognition, Construction Contract, Finishing Percentage, Accounting Standard Statement (PSAK) No. 34.